Takayasu Arteritis Initially Mimicking Infective Endocarditis - Alcelik, Aytekin (Università Cattolica del Sacro Cuore, 2011)
Takayasu’s arteritis (TA) is a chronic inflammatory disease that affects large vessels, predominantly the aorta and its main branches, leading to vessel wall thickening, fibrosis and stenosis. Cardiac and vascular symptoms are also commonly present at disease onset. In TA with thoracic or abdominal involvement, although murmur can be present at physical examination, the pulse difference may be absent. Here, we report a case of TA who initially resembled infective endocarditis and had widespread thoracic murmur.